Ruby under a Microscope: An Illustrated Guide to Ruby Internals - Shaughnessy, Pat (No Starch Press, 2013)
Ruby is a powerful programming language with a focus on simplicity, but beneath its elegant syntax, the language is performing countless unseen tasks. This book gives developers an inside, hands-on look at Ruby's core, using simple diagrams coupled with clear explanations.